What Problem Should Skills Solve? - Allais, Stephanie; Marock, Carmel (International Higher Education, 2024)
Theories of change underpinning skills interventions of donors and development agencies contain tangled webs of assumptions: interventions in relation to youth unemployment often focus on vocational education and training, which is seen as undervalued relative to university education and yet closer to labor markets. However, it is also seen as the problem child of education and training systems. The solution is the problem—and a plethora of interventions are designed in this muddle.